Retirement and Transitions: Empowering Retirees Potentials - Dayang Kartini, Abang Ibrahim; Nor Wahiza, Abdul Wahat (Social Institute of Malaysia, Ministry of Women, Family and Community Development, 2016)
This is a concept paper to review the potential of retirees in helping themselves to walk through a pathway towards retirement. Most of retiring employees are facing problems during the transition period from work to retirement. The loss of job roles, financial insecurity, poor health, dissatisfaction in life and loss of social support are among the factors that lead to apprehension among retiring employees. The purpose of this paper is to examine the potential of retirees from work to retirement and to identify the levels of their knowledge on retirement. The paper is also important in raising public awareness of the critical need of retirees during retirement years and help to outline strategies to encourage the retirees to empower their potentials to be part of the solution. The outcome of the study will hope to change the mindset of individual on retirement and reshape the focus in policy making on supporting life transition holistically.